Determinants of Poverty Levels in Regencies and Municipalities of West Sumatra - Sahri Fitri; Nabila Ramadani; Muhammad Ilham (Rangkiang: Journal of Islamic Economics and Business, 2026)
This study aims to analyze the effect of the Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) growth on poverty levels in regencies and municipalities of West Sumatra Province. This research employs a quantitative approach with an associative research design. The study uses secondary data obtained from the Central Bureau of Statistics (BPS) and other relevant institutions, covering 19 regencies and municipalities in West Sumatra. Panel data regression analysis was applied using statistical software to examine the relationship between the variables. The findings reveal that HDI has a significant and negative effect on poverty levels, as indicated by a significance value of 0.000. This result suggests that improvements in human development contribute to reducing poverty. In contrast, GRDP growth does not significantly affect poverty levels, with a significance value of 0.710. Simultaneously, HDI and GRDP growth significantly influence poverty levels, with a significance value of 0.000. The coefficient of determination (R²) indicates that both variables explain 52.8% of the variation in poverty levels, while the remaining 47.2% is influenced by other factors not included in the model. These findings highlight the importance of improving human development through better education, health services, and living standards as an effective strategy for poverty reduction. Therefore, local governments should prioritize human development policies while promoting inclusive and equitable economic growth to achieve sustainable poverty alleviation.